Creating smart cities: skills and abilities to develop in young people - Volpi, Valentina; Opromolla, Antonio (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
A human-centred approach to smart cities includes the development of skills that allow those who lead urban innovation to achieve positive social impacts. This work presents some of these skills, such as the ability to analyse territorial contexts, to conduct design activities, to adequately apply innovative technologies, for the benefit of a positive experience of the people themselves, as well as the ability to translate ideas in business projects.